Case Report: A case of radioactive iodine-refractory thyroid cancer accompanying cervical lymph node metastasis treated with US-guided RFA combined with 125I seed implantation - Zhai, Yuanpeng; Shao, Yu; Li, Qian (Frontiers in Oncology, 2022)
Background Local control of metastases is critical to improving the life quality of patients with radioactive iodine-refractory (RAIR) thyroid cancer accompanying regional lymph node metastasis. Case report The reported patient suffered from RAIR thyroid cancer accompanying poorly controlled cervical lymph node metastasis. The patient’s lesions were controlled through 125I seed implantation combined with ultrasound-guided radio-frequency ablation (US-guided RFA). Such a combination therapy has not been reported to date. Conclusion This study found US-guided RFA combined with 125I seed implantation to be safe and effective for the control of cervical local metastases in patients with RAIR thyroid cancer.